Anti-locality and subject extraction. Issue 1 (24th August 2020) - Erlewine, Michael Yoshitaka
Abstract : In many languages, Ā-extraction of local subject arguments behaves differently from the extraction of other arguments, for example in triggering specialized morphosyntactic processes or being subject to additional restrictions. I argue that many such interactions are due to an anti-locality constraint on movement, which bans movement which is too short. Subject extraction is often distinguished due to the high canonical position of subjects in their clauses (e.g. Spec, TP), making their movement to the clause edge (e.g. Spec, CP) uniquely in danger of violating the Spec-to-Spec Anti-Locality constraint (Erlewine 2016 ). Concretely, three subject extraction asymmetry behaviors are discussed and analyzed: complementizer-trace effects, subject anti-agreement effects, and bans on subject resumption, including the so-called Highest Subject Restriction. In each case, we observe that the special behavior associated with subject extraction (a) can be obviated by increasing the distance of movement, (b) also applies to exceptionally high non-subjects, and (c) does not correlate with other subjecthood properties. These facts are straightforwardly explained by the anti-locality-based approach to these asymmetries, but are challenging for alternative accounts.